Transforming management using artificial intelligence techniques - Garg, Vikas; Agrawal, Rashmi 1978- (CRC Press, Taylor & Francis Group, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Editors -- Contributors -- Chapter 1 Big Data and Artificial Intelligence: Revolutionizing the Indian Retail Industry with Respect to Virtual Jewelry Stores -- 1.1 Introduction -- 1.2 Big Data and Artificial Intelligence -- 1.3 Benefits of Big Data and Artificial Intelligence -- 1.4 Changes Brought by Big Data and Artificial Intelligence -- 1.5 Problem Statement -- 1.6 Challenges to Big Data and Artificial Intelligence -- 1.7 Big Data and Artificial Management in Marketing -- 1.8 Big Data Use in Marketing -- 1.9 Indian Jewelry Sector -- 1.10 Future of Jewelry Sector in India -- 1.11 SWOT Analysis of a Virtual Store -- 1.12 Literature Review -- 1.13 Future Scope of Big Data and Artificial Intelligence -- Bibliography -- Chapter 2 Unleashing the Potential of Artificial Intelligence in the Education Sector for Institutional Efficiency -- 2.1 Introduction -- 2.2 Meaning of AI -- 2.3 AI and Education Sector -- 2.3.1 AI in the Indian Education Sector -- 2.4 Benefits of Using AI in Education Sector -- 2.5 Challenges with Indian Education Sector -- 2.6 Various AI Tools Used in the Education System -- 2.6.1 AI Tools for Students Affairs -- 2.6.2 AI Tools for Learning and Instructions -- 2.6.3 AI Tools for Administrative Efficiency -- 2.6.4 AI Tools for Students Acquisition -- 2.7 Limitation of AI -- 2.8 Conclusion -- References -- Web Links -- Chapter 3 Reinventing HR in the Era of Artificial Intelligence -- 3.1 Introduction -- 3.2 What Is AI -- 3.3 Importance of AI in HR -- 3.3.1 Robotic Process Automation -- 3.3.2 AI and Recruitment -- 3.3.3 AI and Workforce Planning -- 3.3.4 AI and Brand Building -- 3.3.5 AI and Compensation Management -- 3.3.6 AI in Performance Management -- 3.3.7 AI and Learning and Development -- 3.3.8 AI and Employee Engagement
Description based on publisher supplied metadata and other sources